Remembering Msit No'kmaq: Self-in-Relation Métissage ... - Scott, Michelle Elizabeth (Graduate Studies, 2023)
In the spirit of relationship renewal and repair, I ask the question: How can we begin to enact our responsibilities to learn how to be good relatives to each other, the Land, and our other-than-human kin that is outside of the settler-colonial violence that Canada is built on? I suggest a necessary first step is to take our own self-reflective journey(s) of self-in-relation (Graveline, 1998) to locate our unique kinship networks of relationality and responsibility across time and space. In my research, I centred my embodied personal theory-making (Simpson, 2017), kinship relationality (Donald, 2021) and relationships to Land (Simpson, 2014, 2017; Styres, 2011, 2017, 2019) as a Mi’kmaw and Irish/English woman who has lived in Moh’kins’tsis for twenty-two years, was born and raised in Oniatari:io, and has ancestral and kinship ties to my Mi’kmaw relatives in Ktaqmkuk. Through the process of creating my métissage, I came to know and conceptualize colonial shrapnel as the ways in which colonial violence is ...